Biomechanical analysis of bridge combined fixation system as a novel treatment for the fixation of type A3 distal femoral fractures - Liu, Jianke; Huang, Zhaozhao; Qi, Yubin; Long, Yuntao; Zhang, Yanhui; Liu, Na; Zuo, Guilai; Wang, Wen (Frontiers in Surgery, 2023)
Background: To compare the biomechanical parameters of AO/OTA type A3 distal femoral fractures fixed bilaterally with a bridge combined fixation system (BCFS) and lateral locking compression plate + locking reconstruction plate (LCP + LRP).Methods: Twelve A3 distal femoral fracture models with medial cortical defects of the distal femur were created using synthetic femoral Sawbones. BCFS and LCP + LRP were used for bilateral fixation, with six in each group. Axial compression and torsion tests were performed on the two groups of fracture models to determine their stiffness during axial compression and the Torsional stiffness during torsion tests. Axial compression failure tests were performed to collect the vertical loads of the ultimate failure tests.In the test conducted on the fixed type A3 distal femoral fracture models, the axial stiffness in the BCFS group (group A) (1072.61 ± 113.5 N/mm) was not significantly different from that in the LCP + LRP group (group B) (1184.13 ± 110.24 N/mm) (t = 1.726, P = 0.115), the Torsional stiffness in group A (3.73 ± 0.12 N.m/deg) was higher than that in group B(3.37 ± 0.04N.m/deg) (t = 6.825, P < 0.001),and the ultimate failure test of type A3 fracture model showed that the vertical load to destroy group A fixation (5290.45 ± 109.63 N) was higher than that for group B (3978.43 ± 17.1 N) (t = 23.28, P < 0.05). Notably, intertrochanteric fractures occurred in groups A and B.In the fixation of type A3 distal femoral fractures, the anti-axial compression of the BCFS group was similar to that of the LCP + LRP group, but the anti-torsion was better.